Growth Performance and Nutrient Utilization of Growing Calves with Urea Treated Wheat Straw Based Ration - Kayastha, Trishna B; Dutta, Sanjeeb; Kayastha, Rajeeb B; Deka, Rijusmita S (Indian Journal of Dairy Science, 2012)
An experiment was conducted for a period of 100 days to study the nutrient utilization, feed conversion efficiency, growth performance as well as economics of raising of male calves fed on ration based on urea treated wheat straw. Eight growing male calves of 5 to 6 month of age of 70 to 71 kg body weight were divided into two equal groups viz control (C) and Treatment (T). The animals of group C and group T fed ad lib wheat straw and urea treated wheat straw respectively along with the concentrate mixture. All the animals of both the group were provided with 1 kg green Lucerne. Wheat straw ensiled with 4% urea in 40% moisture for 21 days resulted in improvement in crude protein content from 3% to 8.77%. Significantly higher (p